2020
DOI: 10.3389/fpsyg.2020.00360
|View full text |Cite
|
Sign up to set email alerts
|

Non-Clinical Autistic Traits Correlate With Social and Ethical but Not With Financial and Recreational Risk-Taking

Abstract: Previous research into uncertain and risky decision-making in autism spectrum disorder (ASD) has been inconclusive, with some studies reporting less uncertain and risky decisions by persons with ASD compared to neurotypicals, but other studies failing to find such effects. A possible explanation for these inconsistent findings is that aberrant decision-making in ASD is domain-specific, and only manifests itself in domains related to autism symptomatology. The present study examines this premise by correlating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
2
2
0
Order By: Relevance
“…Autism was associated both phenotypically and genetically with impairment in social functioning consistent with central deficits in social communication in the condition (American Psychiatric Association, 2013 ). In accordance with previous findings (De Groot, 2020 ; South et al., 2014 ), autism also showed a significant relationship with decreased risk raking; though to date no other study has demonstrated our finding of genetic contributions to this overlap. It has been suggested that reduced risk‐taking in autism is related to decreased motivation to engage in social activities, which results in a lack of experience, which may in turn result in wariness for such activities (Chevallier et al., 2012 ; De Groot, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Autism was associated both phenotypically and genetically with impairment in social functioning consistent with central deficits in social communication in the condition (American Psychiatric Association, 2013 ). In accordance with previous findings (De Groot, 2020 ; South et al., 2014 ), autism also showed a significant relationship with decreased risk raking; though to date no other study has demonstrated our finding of genetic contributions to this overlap. It has been suggested that reduced risk‐taking in autism is related to decreased motivation to engage in social activities, which results in a lack of experience, which may in turn result in wariness for such activities (Chevallier et al., 2012 ; De Groot, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…Autism was associated both phenotypically and genetically with impairment in social functioning consistent with central deficits in social communication in the condition (American Psychiatric Association, 2013). In accordance with previous findings (De Groot, 2020;South et al, 2014), autism also showed a significant relationship with decreased risk raking; though to date no other Note: ADHD and autism variables were only used to avoid bias due to using an enriched study sample. The phenotypic correlations estimated with the trivariate model between ADHD or autism and these ERP factors or questionnaires were very similar to the ones reported with bivariate models (Tables 1 and 2).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations